Manganese tetraphenylporphyrin bromide and iodide. Studies of structures and magnetic properties. (1st July 2020) - Bone, Alexandria N.; Stavretis, Shelby E.; Krzystek, J.; Liu, Zhiming; Chen, Qiang; Gai, Zheng; Wang, Xiaoping; Steren, Carlos A.; Powers, Xian B.; Podlesnyak, Andrey A.; Chen, Xue-Tai; Telser, Joshua; et al.
Graphical abstract: Mn–Br/I bonds in Mn(TPP)X are surprisingly longer than Fe–Br/I bonds in Fe(TPP)X (X = Br, I), although Mn(III) and Fe(III) ions have the same radii. Mn(TPP)Br has easy-axis anisotropy ( D < 0), while Mn(TPP)I is easy-plane ( D > 0). Magnitude of the axial anisotropy decreases from Mn(TPP)Cl to Mn(TPP)Br. Highlights: Mn porphyrin halides Mn(TPP)X (X = Br, I) crystallize with a variety of solvents. Mn–X bonds in Mn(TPP)X are surprisingly longer than Fe–X bonds in Fe(TPP)X. Hirshfeld surface analyses of crystal structures reveal intermolecular interactions. Axial anisotropy parameters D < 0 for Mn(TPP)Br and D > 0 for Mn(TPP)I. Magnitude of the axial anisotropy decreases from Mn(TPP)Cl to Mn(TPP)Br. Abstract: Manganese tetraphenylporphyrin bromide and iodide Mn(TPP)X (X = Br, 2 ; I, 3 ; TPP 2− = meso -tetraphenylporphyrinate) are synthetic analogs of Mn(III) geoporphyrins. Crystal structures of 2 and 3 with chloroform in the lattices, Mn(TPP)Br·CHCl3 (2·CHCl3 ), Mn(TPP)I·CHCl3 (3·CHCl3 ), Mn(TPP)I·CDCl3 (3·CDCl3 in a different space group from 3·CHCl3 ), Mn(TPP)I·1.5CHCl3 (3·1.5CHCl3 ), and 2 with dichloromethane in the lattice, Mn(TPP)Br·CH2 Cl2 (2·CH2 Cl2 ), have been determined by single-crystal X-ray diffraction at 100 K or 298 K. Hirshfeld surface analyses of the crystal structures of 2·CHCl3, 2·CH2 Cl2, 3·CHCl3, 3·CDCl3 and 3·1.5CHCl3 have been performed. Surprisingly the Mn(III)–Br and Mn(III)–I bonds in Mn(TPP)X (2 –3 ) are about 0.2 Å (8%) longer than Fe(III)–Br and Fe(III)–I bonds in S = 5/2 Fe(TPP)X (X = Br, 4 ; I, 5 ), although both Mn(III) and Fe(III) ions have the same radii. Magnetic properties of 2 and 3 have been studied by direct current (DC) and alternating current (AC) susceptibility measurements, high-field electron paramagnetic resonance (HFEPR), and inelastic neutron scattering (INS). With four unpaired electrons in Mn(TPP)X (X = Br, 2 ; I, 3 ), the bromide complex 2 in 2·CDCl3 possesses easy-axis anisotropy, as does the chloride analog Mn(TPP)Cl (1 ), with the axial ( D ) and rhombic ( E ) zero-field splitting parameters of D = –1.091(3) cm −1 and | E| = 0.087(2) cm −1 . The iodide complex 3 in 3·CDCl3 becomes easy-plane with D = +1.30(1) cm −1 and | E| = 0.010(5) cm −1 . Axial ZFS parameters D change from −2.290(5) cm −1 in 1, reported earlier, to −1.091(3) cm −1 in 2 and +1.30(1) cm −1 in 3 .